Hydrogen Through Water Electrolysis and Biomass Gasification for Application in Fuel Cells - Y. Kiros; S. Marini; M. Villa; P. Nelli (Renewable Energy and Sustainable Development, 2017)
Hydrogen is considered to be one of the most promising green energy carrier in the energy storage and conversion scenario. Although it is abundant on Earth in the form of compounds, its occurrence in free form is extremely low. Thus, it has to be produced by reforming processes, steam reforming (SR), partial oxidation (POX) and auto-thermal reforming (ATR) mainly from fossil fuels for high throughput with high energy requirements, pyrolysis of biomass and electrolysis. Electrolysis is brought about by passing electric current though two electrodes to evolve water into its constituent parts, viz. hydrogen and oxygen, respectively. Hydrogen produced by non-noble metal catalysts for both anode and cathode is therefore cost-effective and can be integrated into fuel cells for direct chemical energy conversion into electrical energy electricity, thus meeting the sustainable and renewable use with low carbon footprint.